A review of Vietnam's healthcare reform through the Direction of Healthcare Activities (DOHA) - Kyoko Takashima; Koji Wada; Ton Thanh Tra; Derek R. Smith (Komiyama Printing Co. Ltd, 2017)
Abstract Objective This article provides a comprehensive review of the healthcare reform process driven by the Vietnamese Ministry of Health's Direction of Healthcare Activities (DOHA) scheme. Methods We reviewed policy documents relating to DOHA, along with historical literature and background information describing its formation. Results DOHA (Chỉ đạo tuyến in Vietnamese) literally means guidance line or level in English. It requires healthcare facilities at higher government administration levels to support those at lower levels (the four levels being central, provincial, district, and commune), to help lower level hospitals to provide medical services for local communities in primary care settings and reduce the number of patients in higher level (central and provincial) hospitals. Since the 1990s, there have been too many patients attending higher level hospitals, and DOHA has therefore focused on technical skills transfer training to help alleviate this situation. Designated core central hospitals now provide technical skills transfer to provincial hospitals. Professional technical lists for each level of health facility have enabled strong commitment and proactive ownership of the process of training management in both higher and lower level hospitals. Conclusion The DOHA scheme has accelerated the necessary up-skilling of healthcare at lower level public hospitals across Vietnam. These reforms are highly relevant for other countries with limited healthcare resources.